TOURIST REVISIT INTENTION IN POST COVID-19 PANDEMIC: A MODIFIED PERSPECTIVE FROM THE THEORY OF PLANNED BEHAVIOUR (TPB) WITH A FOCUS ON DESTINATION IMAGE - Kenedi, Kenedi; Septiyani, Rini Dwi; Laksana, April; Azhar, Intan Nabila (Gapenas Publisher, 2024)
The impact of the Covid-19 pandemic over the past three years has severely affected the tourism industry, particularly in Banten. The substantial decline in tourist visits is attributed to concerns about various risks. In January 2023, the Indonesian government officially lifted the PPKM (social distancing) regulations, allowing most activities, including tourism, to return to normal. Recognizing this opportunity, it is imperative for all stakeholders to implement effective actions and policies to rejuvenate Indonesian tourism, with a particular focus on Banten. The objective of this study is to investigate the interplay between attitude, subjective norm, and perceived behavioural control. This research adopts a modified perspective from the theory of planned behaviour to understand tourist revisit intentions to Umang Island, Banten, with the mediating variable being destination image. A non-probability sampling technique was employed, and questionnaires were distributed using an online application (Google Form) to 165 respondents who had previously visited Umang Island. The findings reveal that the modified perspective of the theory of planned behaviour, encompassing attitudes, subjective norms, and perceptions of behavioural control, significantly influences destination image. Additionally, the perception of risk significantly impacts tourists' intentions and attitudes towards returning, while subjective norms and perceptions of behavioural control play a significant role in the intention to revisit. Furthermore, attitudes, subjective norms, and perceptions of behavioural control exert a direct influence on tourists' return visits, with destination image serving as a mediating variable